Computationally Efficient 2D-DOA Estimation for Uniform Planar Arrays: RD-ROOT-MUSIC Algorithm - Ye, Changbo; Zhu, Beizuo; Li, Baobao; Zhang, Xiaofei (Transactions of Nanjing University of Aeronautics & Astronautics, 2021)
The problem of two-dimensional direction of arrival（2 D-DOA） estimation for uniform planar arrays（UPAs） is investigated by employing the reduced-dimensional（RD） polynomial root finding technique and 2 D multiple signal classification（2 D-MUSIC） algorithm. Specifically,based on the relationship between the noise subspace and steering vectors,we first construct 2 D root polynomial for 2 D-DOA estimates and then prove that the2 D polynomial function has infinitely many solutions. In particular,we propose a computationally efficient algorithm,termed RD-ROOT-MUSIC algorithm,to obtain the true solutions corresponding to targets by RD technique,where the 2 D root-finding problem is substituted by two one-dimensional（1 D）root-finding operations. Finally,accurate 2 DDOA estimates can be obtained by a sample pairing approach. In addition,numerical simulation results are given to corroborate the advantages of the proposed algorithm.